Oxygen reduction reaction (orr) on bimetallic AuPt and AuPd(1 0 0)–electrodes: Effects of the heteroatomic junction on the reaction paths - Schulte, Erica Daniela (2018)
The seek for materials to enhance the oxygen reduction reaction (orr) rate is a highly relevant topic due to its implication in fuel cell devices. Herein, the orr on bimetallic electrocatalysts based on Au-M (M = Pt, Pd) has been studied computationally, by performing density functional theory calculations. Bimetallic (1 0 0) electrode surfaces with two different Au:M ratios were proposed, and two possible pathways, associative and dissociative, were considered for the orr. Changes in the electronic properties of these materials with respect to the pure metals were acknowledged to gain understanding in the overall reactivity trend. The effect of the bimetallic junction on the stability of the intermediates O 2 and OOH was also evaluated by means of geometrical and energetic parameters; being the intermediates preferably adsorbed on Pt/Pd atoms, but presenting in some cases higher adsorption energies compared with bare metals. Finally, the kinetics of the O–O bond breaking in O 2 ∗ and OOH ∗ adsorbed intermediates in the bimetallic materials and the influence of the Au-M junction were studied by means of the nudge elastic-band method. A barrierless process for the scission of O 2 ∗ was found in Au-M for the higher M ratios. Surprisingly, for Au-M with lower M ratios, the barriers were much lower than for pure Au surfaces, suggesting a highly reactive surface towards the orr. The O–O scission of the OOH ∗ was found to be a barrierless process in Au–Pt systems and nearly barrierless in all Au–Pd systems, implying that the reduction ofO 2 in these systems proceeds via the full reduction of O 2 to H 2 O, avoiding H 2 O 2 formation.